Stabilization of metal-doped magnesium oxide nanoparticles with PAMAM dendrimers to improve alpha-amylase enzyme inhibition - Jaison Jeevanandam; Mara Gonçalves; Rita Castro; Juan Gallo; Manuel Bañobre-López; João Rodrigues (Materials Today Bio)
The present study aimed to synthesize metal-doped magnesium oxide (MgO) nanoparticles to drastically reduce polydispersity and stabilize them with generation 5 of poly(amidoamine) (G5 PAMAM) dendrimers to assess their antidiabetic properties via controlled release. Zinc and silver metals were selected as dopants due to their ionic radius (0.74 Å and 1.16 Å, respectively) for MgO crystal defect reduction (ionic radii – 0.72 Å), allowing for the comparison of the dopants' effect on the nanoparticles’ properties. Later, the resultant nanoparticles were formulated into G5 PAMAM dendrimers, and their amylase inhibition was evaluated and compared with that of non-formulated samples. The results showed that the addition of dopants led to smaller, more stable, and slightly monodispersed spherical, hexagonal, and elongated hexagonal/rod-shaped MgO nanoparticles. The smaller size (∼11–72 nm), surface charge (ca. 17–24 mV), crystallite size ranging from 9.07 nm (Zn-doped MgO) to 17.44 nm (Ag-doped MgO), and distinct shapes have led to enhanced stabilization via G5 dendrimer. Notably, unlike other shapes, spherical nanoparticles were highly stabilized by dendrimers because of the absence of edged atoms. Amylase inhibition assay revealed that dendrimer-stabilized zinc-doped MgO nanoparticles exhibited enhanced inhibitory activity (82.9 %) at 0 h, which decreased to 66.6 % after 24 h, indicating controlled nanoparticle release by the dendrimer. Therefore, this study confirmed the significant role of dendrimer-stabilized metal-doped MgO nanoparticles in enhancing their ability to inhibit enzymes in a controlled manner. These findings led to a novel mechanism that has not been proposed in previous studies.